2021
DOI: 10.1002/phar.2644
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP2B6 genetic polymorphisms with bupropion and hydroxybupropion exposure: A systematic review and meta‐analysis

Abstract: Introduction: Bupropion is metabolized to its active metabolite, hydroxybupropion (HB), by the genetically polymorphic cytochrome P450 2B6 (CYP2B6) enzyme.Despite its significant role in bupropion metabolism, the magnitude of the impact of CYP2B6 genotype on the exposure of bupropion has not been quantified. Objectives:A systematic review and meta-analysis was conducted to quantify the association of bupropion and HB exposure with CYP2B6 variant alleles and genotypedefined metabolizer phenotypes.Methods: MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…BUP 4-hydroxylation is an important bioactivation pathway and a marker of CYP2B6 activity, but the fraction metabolized via 4hydroxylation is small. This is supported by the lack of meaningful effect of CYP2B6 strong inhibitors (Palovaara et al, 2003;Turpeinen et al, 2005) or slow metabolizer of CYP2B6 (Eum et al, 2022) on BUP systemic clearance. The present findings and recent data (Sager et al, 2016) suggest that BUP reduction to THBUP represents the major clearance mechanism of BUP in human liver.…”
Section: Discussionmentioning
confidence: 99%
“…BUP 4-hydroxylation is an important bioactivation pathway and a marker of CYP2B6 activity, but the fraction metabolized via 4hydroxylation is small. This is supported by the lack of meaningful effect of CYP2B6 strong inhibitors (Palovaara et al, 2003;Turpeinen et al, 2005) or slow metabolizer of CYP2B6 (Eum et al, 2022) on BUP systemic clearance. The present findings and recent data (Sager et al, 2016) suggest that BUP reduction to THBUP represents the major clearance mechanism of BUP in human liver.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which efavirenz causes large decrease in the exposure of BUP and its enantiomers is unlikely due to induction of CYP2B6 mediated BUP 4-hydroxylation as the fraction metabolized by CYP2B6 under basal conditions is small ( ∼21%) (Sager et al, 2016). This is further supported by the lack of meaningful effect of modulators of CYP2B6 on BUP systemic clearance despite their marked effect on OHBUP exposure (present data from the inhibition phase; (Eum et al, 2022)). Our recent data (Bamfo et al, 2022) and findings from other authors (Sager et al, 2016) support that BUP reduction, particularly to THBUP and SS-THBUP, represents the major clearance mechanism of BUP and its enantiomers in vitro.…”
Section: Discussionmentioning
confidence: 56%
“…Given the much higher concentration of HB, it is likely to contribute the majority of the pharmacologic activity of bupropion. In vivo pharmacokinetic studies have shown that CYP2B6 PMs (e.g., CYP2B6 * 6/* 6 ) have lower steady-state HB/bupropion metabolic ratios and HB concentrations compared to NMs [ 33 , 35 ], the latter of which was corroborated in a recent meta-analysis [ 36 ]. Lower HB concentrations in plasma have been associated with reduced response to bupropion for depression [ 37 ].…”
Section: Discussionmentioning
confidence: 76%
“…Case report evidence in a CYP2B6 PM taking bupropion illustrated a lack of efficacy with bupropion despite high doses [ 38 ]. Further, based on meta-analysis results showing a 33% decrease of HB area under the plasma drug concentration-time curve in CYP2B6 PMs, the investigators estimated that this reflected an approximately 50% higher bupropion dose requirement to achieve similar HB exposure as in NMs [ 36 ]. Recall that the patient in this case was a CYP2B6 PM and therefore was expected to exhibit less conversion to HB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation